O5-S3.05 Partner notification for STI And HIV: patients' views and experiences of notifying partners. (10th July 2011) - Wayal, S; Cassell, J; Scambler, G; Hart, G; Low, N
Abstract : Background: Partner notification (PN) involves contacting the sexual and needle-sharing partners of patients diagnosed with STI/HIV. Effective PN can prevent onward STI/HIV transmission. However, little is known about the socio-cultural factors affecting PN. We synthesised qualitative literature on views and experiences of PN among people recently diagnosed with STI/HIV and their contacts. Methods: We conducted a systematic search of 4 electronic databases for PN literature from 1990 to August 2009. Meta-ethnography was used to synthesise data from the 16 studies that met our inclusion criteria. We identified key metaphors and themes from individual studies and compared them and their explanations with other studies to enable further interpretations. We then examined the emerging concepts that have implications for STI/HIV PN policy and programs. Results: Our synthesis revealed that PN is influenced not only by type of partnership or infection but also by the socio-cultural, religious, and legal framework governing sex and sexuality. Paradoxically while PN is perceived as altruistic, and as a moral responsibility towards partners, it is also feared as 'social suicide'. 'Breaking the bad news' is perceived as a difficult and potentially troublesome task; however, patient referral is preferred to provider referral. STI/HIV diagnosis invokes 'embodied shame' which can result in non-disclosure, or selective disclosure, or confronting and blaming the partner, especially a main current partner. While the experience of notifying partners is typically not as bad as expected, it occasionally results in violence against women. Injecting drug users felt less able to notify drug-using partners due to legal implications. Provider-led notification is considered protective against fear of violence and social stigma. Conclusions: Meta-ethnography enabled the synthesis of qualitative literature to derive new interpretations and comparative explanations from these data. Our synthesis reveals that PN should be voluntary and confidential and a choice of patient and provider referral methods should be offered. PN programmes should support patients in coping with feelings of shame and guilt to assist notification and facilitate timely testing and treatment of sexual partners. Further research on the sexual health outcomes of PN, its effect on partnerships and how best to reduce the fear of stigma and discrimination associated with STI and PN is needed.